2019
DOI: 10.1111/chd.12789
|View full text |Cite
|
Sign up to set email alerts
|

Ancillary referral patterns in infants after initial assessment in a cardiac developmental outcomes clinic

Abstract: Objective Neurodevelopmental impairment is common after surgery for congenital heart disease (CHD) in infancy. While neurodevelopmental follow‐up of high‐risk patients has increased, the referral patterns for ancillary services following initial evaluation have not been reported. The aim of this study is to describe the rates and patterns of referral at the initial visit to our outcomes clinic of patients who underwent surgery for CHD during infancy. Outcomes Measures The Cardiac Developmental Outcomes Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Full‐text screening of these 193 publications resulted in 35 publications being included in this review. 9 , 13 , 14 , 15 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 The stages of the search and screening process and reasons for exclusion are presented in the PRISMA‐ScR flow diagram (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Full‐text screening of these 193 publications resulted in 35 publications being included in this review. 9 , 13 , 14 , 15 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 The stages of the search and screening process and reasons for exclusion are presented in the PRISMA‐ScR flow diagram (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 35 publications included in the scoping review comprised 33 different studies. Of these, 21 studies examined the implementation of specific programmes or care pathways for neurodevelopmental follow‐up care, 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 56 and 12 studies reported on surveys or overviews of current clinical practices in neurodevelopmental follow‐up. 9 , 13 , 14 , 15 , 16 , 30 , 37 , 41 , 43 , 45 , 46 , 55 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations